2002
DOI: 10.1021/ef020105i
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Effect of Sulfur on Activated Carbon-Catalyzed Hydrocracking of Di(1-naphthyl)methane

Abstract: As a model reaction for coal liquefaction, the hydrocracking of di(1-naphthyl)methane (DNM) was investigated under different reaction conditions. The results show that activated carbon selectively catalyzes DNM hydrocracking and that sulfur has a synergic effect on the activated carbon-catalyzed hydrocracking of DNM. The synergic effect can be ascribed to the catalysis of the activated carbon in H2S dissociation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Sulfur was found to have a synergic effect on the activated carbon-catalyzed hydrocracking of DNM by catalyzing H 2 S dissociation [31]. For CHC of coal-related model compounds under H 2 atmosphere and in the presence of Fe or FeS 2 , adding sulfur promoted the cleavage of bridged bonds in coal-related model compounds [5].…”
Section: Dnm Conversion Over Different Catalystsmentioning
confidence: 98%
“…Sulfur was found to have a synergic effect on the activated carbon-catalyzed hydrocracking of DNM by catalyzing H 2 S dissociation [31]. For CHC of coal-related model compounds under H 2 atmosphere and in the presence of Fe or FeS 2 , adding sulfur promoted the cleavage of bridged bonds in coal-related model compounds [5].…”
Section: Dnm Conversion Over Different Catalystsmentioning
confidence: 98%
“…Compared to the traditional convension processes, catalytic hydroconversion (CHC) could be more feasible to produce chemicals from lignites [12–18] . In recent years, significant efforts have been devoted to directional degradation of coals and coal‐related model compounds (CRMCs) over heterogeneous catalysts because they meet the requirements of high‐performance and eco‐friendly features [19–24] . In particular, solid superacids and supported metals were currently paid attention for catalyzing H + transfer, leading to the cleavage of some bridged bonds, especially CCBBs [25–34] .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] The cleavage of some bridged bonds, especially C ar À C alk bridged bonds (CCBBs) and CÀ O bridged bonds (COBBs) in coals are most important reactions for DCL. The conventional DCL processes performed at high temperatures (400-500 °C) and high hydrogen pressures (15)(16)(17)(18)(19)(20) are not yet competitive economically in addition to significant increase in the yields of both gases and heavy products. [11] Compared to the traditional convension processes, catalytic hydroconversion (CHC) could be more feasible to produce chemicals from lignites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that a specific bond in NMBB was effectively cleaved in the presence of the carbon black. Recently, Ni et al reported that an AC selectively catalyzed the hydrocracking of di(1-naphthyl)methane (DNM), especially in the presence of sulfur . The high activity of the carbonaceous catalysts for the cleavage of specific C−C bonds is of interest, especially for coal liquefaction, because selective coal conversion may be possible with such catalysts.…”
Section: Introductionmentioning
confidence: 99%